Human CD4- invariant NKT lymphocytes regulate graft versus host disease. (2nd November 2018) - Coman, Tereza; Rossignol, Julien; D'Aveni, Maud; Fabiani, Bettina; Dussiot, Michael; Rignault, Rachel; Babdor, Joel; Bouillé, Marie; Herbelin, André; Coté, Francine; Moura, Ivan C.; Hermine, Olivier; et al.
ABSTRACT: Despite increasing evidence for a protective role of invariant (i) NKT cells in the control of graft-versus-host disease (GVHD), the mechanisms underpinning regulation of the allogeneic immune response in humans are not known. In this study, we evaluated the distinct effects of human in vitro expanded and flow-sorted human CD4 + and CD4 − iNKT subsets on human T cell activation in a pre-clinical humanized NSG mouse model of xenogeneic GVHD. We demonstrate that human CD4 − but not CD4 + iNKT cells could control xenogeneic GVHD, allowing significantly prolonged overall survival and reduced pathological GVHD scores without impairing human T cell engraftment. Human CD4 − iNKT cells reduced the activation of human T cells and their Th1 and Th17 differentiation in vivo . CD4 − and CD4 + iNKT cells had distinct effects upon DC maturation and survival. Compared to their CD4 + counterparts, in co-culture experiments in vitro, human CD4 − iNKT cells had a higher ability to make contacts and degranulate in the presence of mouse bone marrow-derived DCs, inducing their apoptosis. In vivo we observed that infusion of PBMC and CD4 − iNKT cells was associated with decreased numbers of splenic mouse CD11c + DCs. Similar differential effects of the iNKT cell subsets were observed on the maturation and in the induction of apoptosis of human monocyte-derived dendritic cells in vitro . These results highlight the increased immunosuppressive functions of CD4 − versus CD4 + human iNKT cells in the context of alloreactivity, and provide a rationale for CD4 − iNKT selective expansion or transfer to prevent GVHD in clinical trials.